2018
DOI: 10.1016/j.ijid.2018.04.3768
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent virulent genes among methicillin resistant Staphylococcus aureus isolates from community settings in Trinidad and Tobago

Abstract: Background:The symptoms of viral and bacterial sore throats are similar, making it difficult to distinguish between them using clinical features alone. We evaluated the Clinical Assessment of Strep Throat (CAST) for predicting beta-haemolytic streptococcal infection. Results were compared to throat cultures that provide a definitive streptococcal diagnosis.Methods & Materials: A total of 440 patients with recent-onset sore throat due to upper respiratory tract infection were randomised to receive a single dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
3
11
1
Order By: Relevance
“…Using the disc diffusion method, no MRSA were observed amongst the isolates from pet canines or their owners. This finding is in agreement with the fact that MRSA colonization in the community in Trinidad and Tobago [69] and other countries [70] is low. Additionally, studies investigating MRSA in households indicates that pets in households where owners were positive were more likely to be MRSA-positive [71].…”
Section: Plos Onesupporting
confidence: 91%
“…Using the disc diffusion method, no MRSA were observed amongst the isolates from pet canines or their owners. This finding is in agreement with the fact that MRSA colonization in the community in Trinidad and Tobago [69] and other countries [70] is low. Additionally, studies investigating MRSA in households indicates that pets in households where owners were positive were more likely to be MRSA-positive [71].…”
Section: Plos Onesupporting
confidence: 91%
“…Similarly, PVL-positive strains accounted for 36% of S. aureus investigated in a study in USA [24]. Our result was lower than the proportion of PVL-positive S. aureus reported in Maiduguri, North East Nigeria (52.1%) [13]; the 61.4% in the Gambia [25], the 58% in Sudan [26], the 73.91% in Colombia [27], the 61.5% in India [28], the 56.2% in Iran [29], the 46.3% in Kazakhstan [30] and the 62.5% in Trinidad and Tobago [31]. In contrast, our result was higher than the prevalence of PVL-positive strains reported from several other studies in Abuja, Nigeria that reported a prevalence of 10.7% among isolates obtained from Maitama District Hospital [14], the 12.7% prevalence reported in Kuwait [8], the 23% reported in Iran [32] and the 18.6% prevalence reported in Brazil [33].…”
Section: Discussioncontrasting
confidence: 73%
“…We speculate that ETSK suppresses the expression of genes encoding S. aureus exotoxin downstream of agrA by inhibiting the gene expression of the agr regulatory system. Due to the down-regulation of agrA gene expression, we have sufficient reasons to infer that the expression of S. aureus exotoxins regulated by RNAIII will be suppressed at both gene and protein levels [38,39]. As a factor that activates RNAIII expression, the downward trend of agrA gene expression is consistent with the inhibition of α-hemolysin and SEs as expected.…”
Section: Etsk Represses Tnf-inducing Activity Of S Aureussupporting
confidence: 66%